Natural Deterioration Processes of Salix psammophila Sand Barriers in Atmospheric Exposure Section - Wang, Ruidong; Dang, Xiaohong; Gao, Yong; Yang, Xia; Liang, Yumei; Zhao, Chen; Duan, Xiaoting (Frontiers in Plant Science, 2022)
The atmospheric conditions of desert environments are important for the protection of Salix psammophila sand barriers, and these conditions can affect and change the structure and performance of the sand barriers, causing them to lose their wind-proofing and sand fixing benefits. However, to assess these issues, we must first examine the key environmental factors that affect the exposure of S. psammophila sand barriers. We must also assess how they affect structural aging and performance. However, these have not been extensively explored, particularly in harsh desert environments. To address this knowledge gap, we examined the macrostructure changes of S. psammophila sand barriers, which were observed by a stereomicroscope, the physical and mechanical properties were tested, and a stoichiometric analysis was conducted. The relative crystallinity and chemical composition changes in the S. psammophila sand barriers were measured by XRD, FTIR, and XPS, and the main degradation factors and processes were discussed. The results showed that the the exposed S. psammophila sand barrier degradation degree was mainly affected by moisture and ultraviolet radiation. Lignin was the main component and source of the photodegradation and photodiscoloration observed of the S. psammophila sand barrier. However, other polysaccharides, such as cellulose and hemicellulose, were less affected by photodegradation. The stress generated by alternating desorption-absorption was the main cause of the expansion and contraction, deformation, cracking, and warping observed pf S. psammophila sand barriers. We also found a series of irreversible changes and losses that occurred, which affected the natural material properties of S. psammophila sand barriers atmospheric exposed to conditions for several years. Exposure times of five years and seven years were the most important time turning point for determining the deterioration of the S. psammophila sand barrier, and our results highlighted the importance of the interactions between atmospheric factors and the exposed atmospheric sections of the sand barrier from the perspective of environmental effects. However, the exact mechanisms of sand barrier deterioration still need further investigation. Nevertheless, our overall findings advanced the current understanding of the environmental effects of S. psammophila sand barriers for ecological restoration and desertification reversal, especially in stressful desert environments.